2008
DOI: 10.1016/j.jsg.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Contractional kink bands formed by stress deflection along pre-existing anisotropies? Examples from the Anglo-Brabant Deformation Belt (Belgium) and the North Dobrogea Orogen (Romania)

Abstract: a b s t r a c tKink bands within two slate belts, the Anglo-Brabant Deformation Belt (Belgium) and the North Dobrogea Orogen (Romania), reveal similar problems with respect to linking kink band geometries to expected palaeostress directions. In the North Dobrogea Orogen, the two opposite kink band sets of two different systems of conjugate kink bands develop for a wide variety of cleavage orientations. In the Anglo-Brabant Deformation Belt, the occurrence of the two opposite kink band sets of a conjugate kink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Two main observations, however, suggest that the vein arrays studied in this paper did not form as a result of kink band development but that the kinking instead is reflecting non-coaxial deformation associated with the pre-existing vein arrays. Firstly, a symmetrical conjugate pair of kink bands forms when the maximum compressive stress during kinking is subparallel to the foliation (Ramsay and Huber, 1987;Srivastava et al, 1998;Debacker et al, 2008). The two sets of kink bands form in the obtuse angle with the maximum compressive stress and are mutually separated by a dihedral angle of ca.…”
Section: Discussion and Kinematic Interpretationmentioning
confidence: 99%
“…Two main observations, however, suggest that the vein arrays studied in this paper did not form as a result of kink band development but that the kinking instead is reflecting non-coaxial deformation associated with the pre-existing vein arrays. Firstly, a symmetrical conjugate pair of kink bands forms when the maximum compressive stress during kinking is subparallel to the foliation (Ramsay and Huber, 1987;Srivastava et al, 1998;Debacker et al, 2008). The two sets of kink bands form in the obtuse angle with the maximum compressive stress and are mutually separated by a dihedral angle of ca.…”
Section: Discussion and Kinematic Interpretationmentioning
confidence: 99%
“…The effort in palaeostress analysis was also extended to single sets of kink bands (Clifford 1968). Debacker et al (2008) cautioned using kink bands to deduce regional palaeostress patterns and suggested that one should not extrapolate the inferred palaeostress outside the region under study.…”
Section: Dynamicsmentioning
confidence: 99%